Agronomic efficiency of polymer-coated triple superphosphate in onion cultivated in contrasting texture soils - Chagas, Wantuir; Guelfi, Douglas; Emrich, Eduardo; Silva, André; Faquin, Valdemar (Revista Ciência Agronômica, 2016)
Information related to phosphate fertilization and coated phosphate fertilizer in onion is scarce. Thus, this study was carried out to evaluate agronomic efficiency, production and nutritional characteristics of triple superphosphate coated with polymers in onion cultivated in contrasting texture soils. Two experiments were carried out under protected conditions in pots containing 5 kg soil. The experimental design was completely randomized with treatments arranged in a 2 x 5 factorial: triple superphosphate (TSP) and polymer-coated triple superphosphate (TSP+P) applied in five phosphorus rates: Dystroferric Red Latosol (LVdf) (clayey) = 0; 100; 200; 400; 800 mg P2O5 kg-1, and Quartzarenic Neosol (sandy) = 0; 75; 150; 300; 600 mg P2O5 kg-1, with three replications. Results indicated that polymer-coated TSP showed no difference for bulb mass and agronomic efficiency for phosphorus fertilization. Agronomic efficiency of phosphorus fertilization decreased with the increase in the amount of phosphorus applied. Phosphorus accumulation for onion bulb cultivated in Dystroferric Red Latosol (LVdf) was higher with the use of polymer-coated triple superphosphate. Growth, production and nutritional characteristics in onion were affected by phosphorus. The highest bulbs mass production and phosphorus accumulation occurred at the doses of 783; 629 mg kg-1 P2O5 (Dystroferric Red Latosol - LVdf), and of 406; 600 mg kg-1 P2O5 (Quartzarenic Neosol -RQ).